Wound Healing - Ahmad, Muhammad (IntechOpen, 2020)
Wound Healing presents recent information and basic knowledge about wound management, including healing mechanisms and actions. It provides a comprehensive overview of the subject, including pathophysiology and clinical and medical management. Chapters cover such topics as negative pressure wound management, hypertrophic scarring, biomaterials derived from plants, insulin use, and modified collagen. This book will help dermatologists, students, surgeons, and physicians who treat patients with wounds.